Teachers' Beliefs and Practices on the Use of ICT in English Language Teaching in Secondary School - Ferisa Indri Hapsari; Santhy Hawany (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aimed to provide an in-depth examination of how English teachers incorporated Information and Communication Technology (ICT) into their English Language Teaching (ELT). This study uncovered the teachers’ beliefs and practices in integrating ICT, explored how their beliefs influence ICT use, and found the obstacles they face when integrating ICT into English language teaching. This study employed a qualitative approach. Four English teachers in the Sidareja district from three state junior high schools and one private junior high school participated in this research. The reason of the researcher in choosing those teachers because of the researcher’s familiarity of the locality, the accessibility of the area that made easy for the researcher to develop quick relationship with the participants. Interviews and classroom observation were used to gain the data. It was done once for each participant. The interview data were analyzed using thematic analysis. The study revealed that the teachers believed about the potential benefits of incorporating technology in the classroom, such as increased student involvement, personalized learning and improved academic outcomes. The classroom observations illustrate the integration of information and communication technology in teaching, emphasizing both the benefits and drawbacks. However, teachers still struggle to implement instructional technology due to some factors namely insufficient facilities and lack of professional development opportunities.